PTH-005 Macroscopic Colonoscopy Findings of Collagenous Colitis; A Three-Centre Experience. (17th August 2016) - Koulaouzidis, A; Sjöberg, K; Bartzis, L; MacNeill, M; Nemeth, A; Yung, DE; Johansson, GW; Fineron, P; Lucendo, AJ; Toth, E
Abstract : Introduction: Microscopic colitis (MC) encompasses 2 entities, collagenous colitis (CC) and lymphocytic colitis (LC). 1 Although (by definition) a histopathological diagnosis, there are occasions when colonoscopy reveals findings such as alteration of the vascular mucosal pattern/innominate grooves, mucosal nodularity and a sequence of mucosal changes from defects/lacerations to cicatricial lesions that are thought to be characteristic of MC, and especially CC. 1, 2 The aim of this study was to evaluate the frequency and type of endoscopic findings in patients diagnosed with CC in two University Hospitals. Methods: Retrospective study. The databases of the Pathology Department of 2 university hospitals in Edinburgh (Scotland) and Malmo (Sweden), and a district general hospital in Spain (Hospital General de Tomelloso) were searched for patients who had been diagnosed with CC between May 2008 and August 2013. Endoscopy reports and endoscopic images were retrieved and reviewed; data on lesions, sedation, bowel preparation (type and effect) and endoscopists' experience were extracted. Categorical data are reported as mean±SD. The Fischer's exact, chi-square and unpaired t tests were used to compare datasets. A two-tailed P value of <0.05 was considered statistically significant. Results: The case notes of 416 patients (96 M/320 F; mean age: 67.1±12.1 years), who had been diagnosed with CC, were collected and reviewed. The colonoscopies had been carried out by senior medical/surgical staff (consultants or associate specialists) in 331 (79.6%). A total of 81 (19.5%) patients had a mix of findings previously described as being suggestive of CC in endoscopy, such as mucosal erythema/oedema (mosaic pattern) (n = 65), colonic mucosa linear defects (lacerations, tears, ulcers/fractures, mucosal furrows) (n = 10), cat-scratch mucosa (n = 4), and cicatricial lesions (n = 3). Although the use of polyethylene glycol (PEG) offers superior quality of bowel preparation effect (as compared to other pre-colonoscopy preparations; P < 0.0001), this was not associated with higher detection rate of all types of macroscopic findings and/or colonic mucosal defects in specific (P = 1.0). Furthermore, mucosal colonic defects had no association with either the experience of the colonoscopist (P = 0.812), or the use of general anaesthesia/propofol (P = 0.53), and/or the use of spasmolytic (hyoscine butylbromide/glucagon) (P = 0.568). Conclusion: A substantial minority of patients with CC (19.5%) had endoscopic findings indicative of CC. The presence of these findings is not associated with procedural factors such as endoscopist's experience, quality of bowel preparation, and/or use of spasmolytic during colonoscopy. References: 1 Koulaouzidis A and Saeed AA. Distinct colonoscopy findings of microscopic colitis: not so microscopic after all? World J Gastroenterol . 2011;17 :4157–4165 2 Suzuki, et al . Usefulness of colonoscopic examination with indigo carmine in diagnosing microscopic colitis. Endoscopy . 2011;43 :1100–1104 Disclosure of Interest: A. Koulaouzidis Grant/research support from: Given Imaging ESGE research grant 2011, Conflict with: Lecture fee(s) from: Dr FalkPharmaUK, Other: Travel support: Dr FalkPharma, Abbott, MSD, K. Sjöberg: None Declared, L. Bartzis Grant/research support from: Hellenic Society of Gastroenterology, M. MacNeill: None Declared, A. Nemeth: None Declared, D. Yung: None Declared, G. Johansson: None Declared, P. Fineron: None Declared, A. Lucendo: None Declared, E. Toth: None Declared